The phase-space dependence of fast-ion interaction with tearing modesaIAEA Technical Meeting paper for submission to Nuclear Fusion. (3rd July 2018) - Heidbrink, W.W.; Bardoczi, L.; Collins, C.S.; Kramer, G.J.; La Haye, R.J.; Lin, D.J.; Muscatello, C.M.; Podestà, M.; Stagner, L.; Van Zeeland, M.A.; Zhu, Y.B.
Abstract: Modulation of various neutral beam sources probes the interaction of fast ions with tearing modes (TM) in the DIII-D tokamak. As measured by electron cyclotron emission, the tearing modes have an island width of ̃8 cm and change phase at the q = 2 surface. (Here, m is the poloidal mode number and n is the toroidal mode number.) Deuterium neutral beam injection by six sources with differing injection geometries produces the fast ions. To study the interaction in different parts of phase space, on successive discharges, one of the six sources is modulated at 20 Hz to populate different fast-ion orbits. The modulation only changes the island width by a few millimeters, implying that any fast-ion effect on mode stability is below detection limits. When compared to the expected signals in the absence of TM-induced transport, both the average and modulated neutron signals deviate, implying that fast-ion transport occurs in much of phase space. Fast-ion D α (FIDA) measurements detect reductions in signal at wavelengths that are sensitive to counter-passing ions. Neutral particle analyzer data imply poor confinement of trapped fast ions. Calculations of the expected fast-ion transport that use measured TM properties successfully reproduce the data.